Resistive drift instabilities for thermal and non-thermal electron distributions in electron-ion plasma. Issue 12 (December 2018) - Rehman, Umer
Abstract: Local dispersion relations for resistive drift mode in a nonuniform magnetize plasma are derived for thermal and non-thermal distribution of electrons. The coupled mode equations are obtained by using Braginskii's transport equations for ions and electrons with thermal as well as non-thermal (Cairns and kappa) distribution for electrons. The dispersion relations are then analyzed both analytically as well as numerically for all distributions. It is found that growth rate is highest for Maxwellian, Intermediate for kappa and lowest for Cairns distribution. It has been found that increasing values of Γ (which estimate population of non-thermal electrons) for Cairn distributed electrons are able to stabilize the mode. Furthermore, increasing the values of κ (which is spectral index) for the kappa distributed electrons have destabilizing effects on the mode. The result might be useful in the interpretation of electromagnetic fluctuations in nonuniform magneto-plasma in which resistivity is a key element in calculation of drift instabilities in the presence of thermal or nonthermal electron distributions, such systems are extensively observed in laboratory as well as space plasma.